Performance of the SCORTEN in Taiwanese patients with Stevens-Johnson syndrome and toxic epidermal necrolysis - Yu-Ling Ho; Yun-Ting Chang; Yu-Tseng Chu; Shiao-Chi Wu (Dermatologica Sinica, 2010)
Background: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare drug-related skin conditions that are potentially life-threatening with a 20–30% mortality rate. A severity-of-illness score specified for SJS and TEN, SCORTEN, was developed in 2000. Until now, no study of SCORTEN has been conducted in Asian with SJS or TEN. The goal of the present study is to evaluate the performance of SCORTEN in predicting in-hospital mortality in Taiwanese patient with SJS or TEN. Methods: A sample of 51 patients with the diagnosis of SJS or TEN was reviewed from the chart. Performance of the SCORTEN was assessed using logistic regression. Results: The hospital mortality rate predicted by the SCORTEN was similar to the observed mortality rate. The performance of SCORTEN was well on each of the first 5 days of hospitalization, and best on the first day. There were two cases with active tuberculosis and five with diabetes mellitus among our eight deceased patients. Conclusion: The performance of SCORTEN is well in Taiwanese patients with SJS or TEN, especially on the first day of admission. The SCORTEN predicts a relatively accurate in-hospital mortality rate. We suggest that the SCORTEN should always be obtained during the first 24 hours, and can be repeated if the patient's condition deteriorates quickly in the first 5 days. Pre-existing conditions, such as tuberculosis and pre-existing diabetes, may need more consideration in future studies.